Specific genomic alterations and aggressive clinical features of sporadic thyroid carcinomas in children and adolescents: findings from an in-house cohort study - Tan, Gongxun; Wang, Yuguo; Zhang, Guoliang; Wang, Xian; Ren, Yongzhen; Gu, Qian; Xu, Feiju; Mao, Zhenwei; Shi, Chunhe; Wang, Hui; Wu, Ting; Wei, Xi; et al. (Frontiers in Endocrinology, 2025)
IntroductionPapillary thyroid carcinoma is the most common pathological subtype of thyroid cancer in both children/adolescents (TCCA) and adults (TCA). TCCA manifests more aggressive and invasive behaviors than TCA, which may be attributed to specific genomic alterations. MethodsTo better understand the specific molecular, pathological and clinical manifestations of TCCA, we retrospectively analyzed a cohort of 60 patients with sporadic papillary thyroid carcinoma, including 20 TCCAs and 40 TCAs. Fine-needle aspiration tissue samples from these cases were analyzed using next-generation sequencing. Demographics, ultrasound features, postoperative pathology and radiation exposure history were compared between TCCAs and TCAs. To validate our findings, we integrated data from 28 prior studies, resulting in a larger cohort of 1,483 sporadic TCCAs. ResultsMultiple gene mutations were more prevalent in TCCAs than TCAs (p=0.013), such as BRAFV600E coexisting with KMT2 family genes or PTEN. Although BRAFV600E was the most common single nucleotide variant in TCCAs (25%, 5/20), its prevalence was significantly lower than in TCAs (95%, 38/40, p<0.0001). RET oncogenic fusions were detected exclusively in TCCAs, with an incidence of 20% (4/20). Compared with TCAs, TCCAs were associated with larger tumor diameters (p<0.001), more advanced tumor staging (T3–T4, p<0.001; N2, p=0.002), higher incidence of extrathyroidal extension (TCCA: 25%, TCA: 5%, p=0.036) and more frequent lymph node metastasis (TCCA: 70%, TCA: 27.5%, p=0.0024). Importantly, TCCAs harboring BRAFV600E alongside other mutations (e.g., ATM, PTEN or KMT2 family genes) exhibited more severe clinical manifestations, including larger tumors and higher rates of lymph node metastasis, compared with those harboring BRAFV600E alone.DiscussionTCCAs exhibit more aggressive and invasive clinical manifestations than TCAs, particularly in cases with RET fusions or BRAFV600E coexisting with other point mutations. Targeted comprehensive molecular profiling may aid in the diagnosis and treatment of TCCA.